1949
DOI: 10.1017/s0080456800019104
|View full text |Cite
|
Sign up to set email alerts
|

XXIV.—The Innervation of the Human Quiescent Nipple, with Notes on Pigmentation, Erection, and Hyperneury

Abstract: It has been known from antiquity that involution of the uterus is aided by putting the child to the breast, and the work of Moir (1933) has demonstrated conclusively that suckling brings about waves of contraction of the puerperal uterus. Since suckling must necessarily involve stimulation of the nipple, it seemed of interest to know what sensory apparatus is present in the nipple to receive these stimuli. While histological studies of the mammary gland itself have been numerous, only slight attention has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
5

Year Published

1952
1952
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 9 publications
0
12
0
5
Order By: Relevance
“…In the early 1950s, the nipple was considered to have a nerve supply from just sympathetic origin contributing only to pain with an absence or paucity of receptors for tactile, moving sensation (Meissner corpuscles) or pressure (Pacinian corpuscles). 16 By the 1980s, the literature suggested that the possible loss of sensitivity postoperatively was due to damage of the lateral intercostal nerves before they course upward over the breast parenchyma and pass subcutaneously to the nipple-areola complex. 2,3 This conjecture of possible damage to the lateral intercostal nerves was extrapolated from cadaver dissection and the nerve-sensitivity testing performed using crude touch.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1950s, the nipple was considered to have a nerve supply from just sympathetic origin contributing only to pain with an absence or paucity of receptors for tactile, moving sensation (Meissner corpuscles) or pressure (Pacinian corpuscles). 16 By the 1980s, the literature suggested that the possible loss of sensitivity postoperatively was due to damage of the lateral intercostal nerves before they course upward over the breast parenchyma and pass subcutaneously to the nipple-areola complex. 2,3 This conjecture of possible damage to the lateral intercostal nerves was extrapolated from cadaver dissection and the nerve-sensitivity testing performed using crude touch.…”
Section: Discussionmentioning
confidence: 99%
“…) The only publications since 1908 which specifically allude to unencapsulated nerve endings in the dermis of which we are aware, are concerned with the innervation of the human nipple, gum and hard palate (Cathcart, Gairns & Garven, 1948; Gairns & Aitchison, 1950; Gairns,195 I). .…”
mentioning
confidence: 99%
“…Garven and Gairns modification now given was evolved when working on the innervation of the human nipple [Cathcart, Gairns and Garven, 1948], and has special advantages in the study of the peripheral sympathetic fibres. In that investigation both fresh surgical specimens and early autopsy material were used.…”
mentioning
confidence: 99%